Experience of Using High-Frequency Lung Ventilation during Cardiopulmonary Bypass in Cardiac Surgery - A. Yu. Kirillov; A. G. Yavorovskiy; M. A. Vyzhigina; R. N. Komаrov; V. A. Aliev; P. S. Bаgdаsаrov; D. A. Yavorovskаya; R. S. Kushanov; E. A. Laricheva (Вестник анестезиологии и реаниматологии)
The incidence of various postoperative complications including pulmonary ones is at a high level in a cardiac surgery.The objective: to evaluate the effectiveness of high-frequency lung ventilation during cardiopulmonary bypass as a preventive measure for postoperative pulmonary complications compared to low-volume lung ventilation.Subjects and Methods. 60 patients undergoing cradiac surgery were included in the study. In HF Group (HF ventilation with airway pressure control at the frequency of 300/min, the ratio of duration of inhalation and exhalation is 1:2, mean airway pressure is 8 mbar) and VC Group (lung ventilation during CPB with parameters: tidal volume is 3 ml/kg, respiratory rate is 6/min, and positive end-expiratory pressure is +5 cm H2O).Results. No significant difference in the analysis of the oxygenation index were observed between groups. Frequency of pulmonary atelectasis on chest radiology in postoperative period made 3 (9%) in VC Group and 4 (12%) HF Group (p = 0.71). The frequency of intraoperative recruiting lung maneuvers was 5 (16%) in VС Group and 6 in HF Group (18%) (p = 0,75). The duration of postoperative ventilation did not differ between the groups.Conclusion. HF mechanical ventilation during CPB has no significant advantage over low-volume mechanical ventilation. HF mechanical ventilation and low-volume mechanical ventilation has the same protective effect on the oxygenating function of the lungs after CPB.